Impulse control disorders are associated with lower ventral striatum dopamine D3 receptor availability in Parkinson's disease: A [11C]-PHNO PET study. (September 2021) - Pagano, G.; Molloy, S.; Bain, P.G.; Rabiner, E.A.; Ray Chaudhuri, K.; Brooks, D.J.; Pavese, N.
Abstract: Introduction: Reduced postsynaptic D3 dopaminergic receptor availability has been reported in the ventral striatum of pathological gamblers without Parkinson's disease (PD) and in patients with PD and impulse control disorders (ICD). However, a direct relationship between ventral striatum D3 dopaminergic receptors and the severity of ICD in PD patients has not yet been proven using a validated tool for ICD in PD, such as the Questionnaire for Impulsive-Compulsive Disorders in Parkinson's disease-Rating Scale (QUIP-RS). In this pilot study, we investigated the relationship between ventral striatum D3 dopamine receptor availability and severity of impulse control disorder (ICD) in Parkinson's disease (PD). Methods: Twelve patients were assessed with PET and the high affinity dopamine D3 receptor radioligand [ 11 C]-PHNO. Severity of ICD was assessed with the QUIP-RS. Results: We found that lower ventral striatum D3 receptor availability measured with [ 11 C]-PHNO PET was associated with greater severity of ICD, as measured by the QUIP-RS score (rho = −0.625, p = 0.03). Conclusion: These findings suggest that the occurrence and severity of ICD in Parkinson's disease may be linked to reductions in ventral striatum dopamine D3 receptor availability. Further studies in larger cohort of patients need to be performed in order to confirm our findings and clarify whether lower ventral striatum D3 receptor may reflect a pharmacological downregulation to higher dopamine release in ventral striatum of patients with ICD or a patients' predisposition to ICD. Highlights: Impulse control disorders are common in individuals with Parkinson's disease. The cause is unknown but there is a predisposition to impulse control disorders. Lower D3 receptor correlated with greater impulse control disorders severity. Higher dopamine release in predisposed individuals might explain this finding. Novel drugs restoring D3 receptors might reduce impulse control disorders.